SISTEM MONITORING BERAT DAN TAG RFID PADA ALAT RECORDING BOBOT BADAN SAPI BERBASIS INTERNET OF THINGS - Effan Akbartama; Adharul Muttaqin; Onny Setyawati (Jurnal Mahasiswa TEUB, 2022)
Recording is all kinds of recording activities such as identification activities, genealogy records, production and reproduction records, as well as health records. This activity is the basis for the fattening process on cattle farms. One of the important measurement criteria in animals is weight. Weight measurements must be accurate and also require an adequate monitoring system so that the recording results are easy to monitor. Accurate and easy-to-monitor recording results will make maintenance management optimal so as to make optimal growth of cattle as well. However, the current traditional breeder recording equipment used monitoring system is still not optimal. Therefore, the purpose of this research is to design a Monitoring System for Cattle Body Weight Recording Devices Based on the Internet of Things. The system is equipped with realtime data transmission which is stored in a database and displayed on the website. The database is created using services from firebase. With IoT monitoring, cattle weight measurement values, RFID tag data, measurement time, and age can be accessed via a website that aims to make it easier for users to view realtime data and recapitulate measurement data. The results of the research conducted, the system runs according to design. In the test of sending heavy data, RFID tag data, time and date into firebase the success rate is 100% and website functionality also has 100% success. The data obtained from testing the delay in sending data to firebase obtained an average delay of 0.97 seconds. the highest delay value is 1.36 seconds and the lowest value is 0.72 seconds. The throughput on the system is 1990 bits/sec. Keywords : Recording, Weight, Monitoring, Internet of Things, firebase